South-East Asian Countries Defense Diplomacy Strategy for Capacity Building Study Case of Philipines - Putra, Calvin Anthony; Anwar, Syaiful; Duarte, Editha Praditya (Universitas Pahlawan Tuanku Tambusai, 2024)
This study explores the changing dynamics of defense and diplomacy in the Philippines amidst the escalating rivalry between the United States (US) and China. Due to its strategic geographical location, the Philippines faces susceptibility to the consequences of this rivalry. The primary focus is on the Philippines' comprehensive defense diplomacy strategy, which has been in practice since the Ramos administration. Rooted in the United Nations Convention on the Law of the Sea (UNCLOS), the Philippines pursues a law-centric diplomacy, notably through the 2009 Philippine Baselines Law. The strategic framework draws inspiration from Harry R. Yarger's